Resiliensi pada Penyintas Banjir Ditinjau dari Tawakal dan Kecerdasan Emosi - Ridha Habibah; Subekti Dwi Lestari; Sherli Kurnia Oktaviana; Fuad Nashori (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
Resilience by people affected by natural disasters is very important. Disaster is an extreme thing that can make a person depressed, anxious, stressed, and somatisasi. Individuals who pay attention to belief in God, cognitive and positive affective of the things it faces, will affect its resilience. This study aims to determine the resilience of flood survivors in terms of tawakal and emotional intelligence. The research subjects were flood survivors aged 20-60 , 53 people, obtained by using quotum technique. Data collection used three psychological scales: Resilience Scale, Emotional Intelligence Scale, and Tawakal Scale. The methods for data analysis were multiple linear regression and partial correlation. The results showed significant relationship between tawakal and emotional intelligence together against resilience. The relationship between tawakal and resilience is significant but the relationship between emotional intelligence and resilience is not significant. Further analysis shows emotional intelligence has indirect relationship mediated by tawakal variable.